Detrital zircon U–Pb geochronology of a Cenozoic foreland basin in Northeast India: Implications for zircon provenance during the collision of the Indian and Asian plates. (13th November 2018) - Baral, Upendra; Lin, Ding; Goswami, Tapos Kumar; Sarma, Mondip; Qasim, Muhammad; Bezbaruah, Devojit
Abstract: Geochronology is useful for understanding provenance, and while it has been applied to the central and western Himalaya, very little data are available in the eastern Himalaya. This study presents detrital zircon U–Pb ages from the late Palaeocene–Eocene Yinkiong Group in NE India. The samples are from the late Palaeocene to early Eocene Lower Yinkiong Formation, and the Upper Yinkiong Formation deposited during the early to mid‐Eocene within the Himalayan foreland basin. The U–Pb ages of the detrital zircon within the Lower Yinkiong Formation are older than late Palaeozoic, with a cratonic and early Himalayan Thrust Belt affinity, whereas the Cenozoic grains in the Upper Yinkiong Formation indicate a Himalayan Thrust Belt source and possibly a granitic body within the Asian plate. The shift of the sources and the changes in the foreland basin system strongly suggest that the India–Asia collision in the Eastern Himalaya began before or immediately after the deposition of the Upper Yinkiong Formation, i.e., within the early Eocene ( c . 56 to 50 Ma).